Public health impact model estimating the impact of introducing an adjuvanted recombinant zoster vaccine into the UK universal mass vaccination programme. Issue 5 (5th May 2019) - van Oorschot, Desirée A M; Hunjan, Manjit; Bracke, Benjamin; Lorenc, Stéphane; Curran, Desmond; Starkie-Camejo, Helen
Abstract : Objectives: In 2013, the herpes zoster (HZ) immunisation programme was introduced in the UK, recommending vaccination of adults 70 years of age (YOA) with the zoster vaccine live (ZVL), the only vaccine available at the time. The recently approved adjuvanted recombinant zoster vaccine (RZV) has a substantially different clinical profile that may offer additional benefits. This study aimed to 1) assess the public health impact (PHI) of introducing RZV in the UK compared with the current vaccination strategy and 2) explore via scenario analyses the optimal age group of vaccination in terms of PHI. Design: A previously developed health economic model was adapted to the UK setting. Setting: Calculations were based on efficacy data from pivotal clinical trials, HZ incidence and postherpetic neuralgia (PHN) probability from a UK study and HZ-associated complication rates from published literature. Population: The base-case population considered a 2018-projected UK vaccination cohort of individuals 70 YOA. Interventions: Vaccination with ZVL or RZV, assuming a first-dose coverage of 48.3% for both vaccines and 70% compliance for the second dose of RZV. Outcome measures: Outcomes included reduction of HZ and PHN cases, complications and the use of healthcare resources over a life-time horizon. The impact of coverage and second-dose compliance was also explored. Results: Compared with no vaccination, RZV would lead to a reduction of 30 262 HZ and 5409 PHN cases while ZVL would lead to a reduction of 7909 HZ and 3567 PHN cases. The number needed to vaccinate to prevent 1 HZ case is 12 with RZV and 45 with ZVL. The highest PHI with RZV could be achieved in individuals 60 or 65 YOA. Conclusion: Under the model assumptions, RZV is predicted to avert more HZ and PHN cases compared with ZVL. Results were robust under different scenario and sensitivity analyses.